The effect of gestational weight gain on perinatal outcomes among Chinese twin gestations based on Institute of Medicine guidelines - Dongxin Lin (BMC Pregnancy and Childbirth, 2019)
Abstract Background Gestational weight gain (GWG) has implications for perinatal outcomes, the guidelines for maternal weight gain, however, remain understudied among twin pregnancies. This study aimed to assess the associations between perinatal outcomes and GWG among twin pregnancies, based on the US institute of Medicine (IOM) 2009 guidelines. Methods A retrospective cohort study of pregnant women with viable twins ≥26 weeks of gestation, was conducted in Foshan, China, during July 2015 and June 2018. Maternal BMI was categorized based on Chinese standard and GWG was categorized as below, within and above the IOM 2009 recommendations. Underweight women were excluded for analysis. Perinatal outcomes were compared among these groups. To assess the independent impact of GWG on the perinatal outcomes, conventional multivariable regression and general estimated equation (GEE) were utilized for maternal outcomes and neonatal outcomes, respectively. Results A total of 645 mothers with twin pregnancies were included, of whom 15.0, 41.4 and 43.6% gained weight below, within and above guidelines, respectively. Compared to weight gain within guidelines, inadequate weight gain was associated with increased risks in spontaneous preterm birth < 37 weeks (aOR:3.55; 95% CI: 1.73–7.28) and < 35 weeks (aOR:2.63; 95% CI: 1.16–5.97). Women who gained weight above guidelines were more likely to have gestational hypertension disorder (aOR: 2.36; 95% CI: 1.32–4.21), pre-eclampsia (aOR: 2.59; 95% CI: 1.29–5.21) and have fetuses weighted >90th percentile and less likely to have fetuses weighted < 2500 g and < 1500 g. Conclusions Maintenance of gestational weight gain within the normal range could decrease the risk of adverse perinatal outcomes. However, the causality between pre-eclampsia and gestational weight gain requires further investigations.